Industrial and Commercial Districts of a Town: History and Present - Darulová, Jolana (Lidé města, 2008)
Social and professional groups create a significant part of an urban community. It can be proved that business activities have existed ever since the Middle Ages in the town of Banská Bystrica: there were activities connected with mining and metallurgy (mines, smiths, etc.) and there were sawmills, textile factories, mills, and distilleries in the period of the establishment of manufactories and factories. Powerful local business families were formed in this context. The period between the two world wars was especially prosperous. A number of trades and shops were reconstructed. Later, during the socialist period, the tradition was interupted and, after 1989, business activities did not continue in the tradition of family business. Commercial activities in the town have now been influenced and homogenized by the establishment of famous-brand retail chains and restaurants offering foreign cuisine. A professional group of miners in Banská Štiavnica had helped to create mining traditions. These traditions have been reproduced today – even after mine closings. Social activities of the town also reflect tradition.